(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
The.main.aim of our paper is introduced.new.conceptofcompactspaceis called wb-compact.Space, for this aim, the concept of b-compact space and w-compact space introduced and find that every is relationships among compact, b-compact, w-compact spaces and the converse is not not true in generals and we define nearly ? b-compact space and we prove some results about subject.